2008
DOI: 10.1111/j.1445-2197.2007.04394.x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength of Surgical Knots in Abdominal Wound Closure*

Abstract: Abdominal wound dehiscence is a surgical catastrophe that can be attributed to patients or technical factors. The technical properties of the monofilament sutures and knots that are commonly used in abdominal closure are poorly understood. The aim of this study was to compare the tensile strength of monofilament sutures tied with conventional knots. To do this, the knot-holding capacity of four types of knots (square, surgeons', Aberdeen and loop) were tested using three types of gauge 1 monofilament suture, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 5 publications
1
26
0
1
Order By: Relevance
“…Previously the continuous running closure of an abdominal wound with a absorbable monofilament suture with a length to wound length ratio of 4:1 has been recommended (Wissing et al, 1987;Jenkins, 1976;van 't Riet et al, 2002;Gislason et al, 1995). The initial anchoring knot should be a loop knot, and each tissue bite should be taken greater than 10 mm from the cut edge, and the final knot should either be an Aberdeen knot or surgeons knot (Fong et al, 2008). However recent studies have identified that excessive tissue bites are associated with unacceptable increased rates of wound complications, and as such it is recommended to reduce tissue bites to less than 1 mm, additionally the length to wound length ratio will need to be altered to facilitate this (Cengiz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously the continuous running closure of an abdominal wound with a absorbable monofilament suture with a length to wound length ratio of 4:1 has been recommended (Wissing et al, 1987;Jenkins, 1976;van 't Riet et al, 2002;Gislason et al, 1995). The initial anchoring knot should be a loop knot, and each tissue bite should be taken greater than 10 mm from the cut edge, and the final knot should either be an Aberdeen knot or surgeons knot (Fong et al, 2008). However recent studies have identified that excessive tissue bites are associated with unacceptable increased rates of wound complications, and as such it is recommended to reduce tissue bites to less than 1 mm, additionally the length to wound length ratio will need to be altered to facilitate this (Cengiz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of wound complications is complex and multi-factorial; both systemic and local factors are involved. However the role of surgical error and poor technique are increasingly becoming recognised as fundamental factors in the development of wound complications (van Rijssel et al, 1990;Fong et al, 2008). Accordingly the area of wound closure research is of particular interest, as these factors are related to wound complications and are directly modifiable by the surgeon (Mudge and Hughes, 1985;Sugerman et al, 1996;Pavlidis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 Some suture materials have an inherently low coefficient of friction, meaning the knot will likely untie at a lower load. Special coatings allow sutures to pass more easily through tissues by lowering the coefficient of friction and improving handling characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The authors acknowledged that types of suture materials (braided or multifilament), effect of knot placement, 11 and accelerated hydrolysis of different types of suture materials in different types of urine were important parameters that were not tested but should be taken into account in determining the effects of suture degradation. To study the effect of above on suture tensile strength and anastomosis integrity, further animal studies should be conducted to provide accurate simulation of in vivo reaction between suture tensile strength and degradation for different suture materials in different types of tissues.…”
Section: Discussionmentioning
confidence: 99%